Rapid, Sensitive, and Species-Specific Detection of Conventional and Recombinant Herpesvirus of Turkeys Vaccines Using Loop-Mediated Isothermal Amplification Coupled With a Lateral Flow Device Readout - Mescolini, Giulia; Baigent, Susan J.; Catelli, Elena; Nair, Venugopal K. (Frontiers in Veterinary Science, 2022)
Marek’s disease, an economically important disease of chickens caused by virulent serotype 1 strains of the Mardivirus Marek’s disease virus (MDV-1), is effectively controlled in the field by live attenuated vaccine viruses including herpesvirus of turkeys (HVT) – both conventional HVT (strain FC126) and, in recent years, recombinant HVT viruses carrying foreign genes from other avian viruses to protect against both Marek’s disease and other avian viral diseases. Testing to monitor and confirm successful vaccination is important, but any such test must differentiate HVT from MDV-1 and MDV-2, as vaccination does not prevent infection with these serotypes. Endpoint and real-time PCR tests are widely used to detect and differentiate HVT, MDV-1 and MDV-2 but require expensive specialist laboratory equipment and trained operators. Here, we developed and validated two tube-based loop-mediated isothermal amplification tests coupled with detection by lateral flow device readout (LAMP-LFD): an HVT-specific test to detect both conventional and recombinant HVT strains, and a second test using novel LAMP primers to specifically detect the Vaxxitek® recombinant HVT. Specificity was confirmed using DNA extracted from virus-infected cultured cells, and limit of detection was determined using plasmid DNA carrying either the HVT or Vaxxitek® genome. The LAMP-LFD tests accurately detected all HVT vaccines or Vaxxitek® only, in crude DNA as well as purified DNA extracted from field samples of organs, feathers, or poultry house dust that were confirmed positive for HVT by real-time PCR. These LAMP-LFD tests have potential for specific, rapid, simple, and inexpensive detection of HVT vaccines in the field.